2021
DOI: 10.1302/1863-2548.15.210081
|View full text |Cite
|
Sign up to set email alerts
|

Defining Length Stability in Paediatric Femoral Shaft Fractures Treated with Titanium Elastic Nails

Abstract: Introduction Optimal paediatric femoral shaft fracture patterns or lengths amenable to titanium elastic nail stabilization have not been well defined. The purpose of this study is to identify radiographic parameters predictive of treatment failure with flexible intramedullary nails based upon fracture morphology. Methods A retrospective review was performed of all femoral shaft fractures treated with flexible intramedullary nails over a five-year period. All patients with at least six weeks of postoperative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, more recent studies reported no significant difference in complication rates between length stable and unstable PDFF. [10][11][12] Over the last 2 decades, our indications for the use of ESIN in PDFF have also expanded from the simple transverse or short oblique fractures toward more unstable fracture patterns in line with the literature. The majority of PDFF have been treated with ESIN in our institution, regardless of the stability of the fracture pattern.…”
mentioning
confidence: 77%
“…On the other hand, more recent studies reported no significant difference in complication rates between length stable and unstable PDFF. [10][11][12] Over the last 2 decades, our indications for the use of ESIN in PDFF have also expanded from the simple transverse or short oblique fractures toward more unstable fracture patterns in line with the literature. The majority of PDFF have been treated with ESIN in our institution, regardless of the stability of the fracture pattern.…”
mentioning
confidence: 77%
“…Andreacchio et al reported that higher weight (> 50 kg) as a potential risk factor associated with poor clinical outcomes 29 . Shieh et al defined that unstable fracture pattern as fracture length greater than twice the cortical width 30 . In the present study, we could not reach the weight information of the patients at the time of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The current study by Nixon and his St Louis coauthors 8 in this issue of J Orthop Trauma adds to the growing body of literature (at least the seventh study) that supports the use of ESIN in unstable femoral shaft fractures. 9–14 Using the same definition of unstable as Sink et al did in 2005, Nixon et al compared 63 stable and 43 unstable femoral shaft fracture patients and found no difference in major complication rates (12.7% and 11.6%, respectively). Nail tip irritation was not defined as a major complication—which is reasonable because the nails are usually not intended for permanent implantation.…”
mentioning
confidence: 98%